Was.Is.Always: South to North. On Route to an International Indigenous Design Charter: Greenland Workshop - Russell Kennedy; Meghan Kelly (2017)
Was.Is.Always: South to North, a community led workshop in Nuuk Greenland brought together researchers, students, industry, and other organisations involved or interested in Indigenous design. The primary aim of the workshop was to progress discussion towards the realisation of an International Indigenous Design Charter, outlining the appropriate use of Indigenous knowledge in commercial communication design practice.